2020
DOI: 10.1002/alz.12091
|View full text |Cite
|
Sign up to set email alerts
|

Age‐stratified longitudinal study of Alzheimer's and vascular dementia patients

Abstract: Introduction Similar symptoms, comorbidities and suboptimal diagnostic tests make the distinction between different types of dementia difficult, although this is essential for improved work‐up and treatment optimization. Methods We calculated temporal disease trajectories of earlier multi‐morbidities in Alzheimer's disease (AD) dementia and vascular dementia (VaD) patients using the Danish National Patient Registry covering all hospital encounters in Denmark (1994 to 2016). Subsequently, we reduced the comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 50 publications
0
34
0
1
Order By: Relevance
“…Multimorbidity was defined as the presence of 2+ chronic conditions in all but six studies. Of these six, one study 107 defined multimorbidity as the co-occurrence of 3+ conditions and four 111 , 116 , 118 , 119 did not specify a definition (Supplementary Table S6). However, all authors referenced consideration of 2+ conditions in their prose and/or tables.…”
Section: Resultsmentioning
confidence: 99%
“…Multimorbidity was defined as the presence of 2+ chronic conditions in all but six studies. Of these six, one study 107 defined multimorbidity as the co-occurrence of 3+ conditions and four 111 , 116 , 118 , 119 did not specify a definition (Supplementary Table S6). However, all authors referenced consideration of 2+ conditions in their prose and/or tables.…”
Section: Resultsmentioning
confidence: 99%
“…National patient registers covering hospital only have previously been used in epidemiologic studies about dementia. 23 We adjusted for patient characteristics, comorbidity, operation year, and socioeconomic factors in our statistical models. It would have been interesting also to include genetic factors, such as apolipoprotein E (APOE) ε4, which is a significant risk factor for both dementia and coronary artery disease, [24][25] but genetic information is not included in national registries and databases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study has reported that pneumonia-caused death was higher in Alzheimer’s disease compared to vascular dementia [ 48 ], suggesting a potential difference in patients’ respiratory and immune functions among distinct subtypes of dementia. The development of vascular dementia is closely associated with atherosclerosis and cardiovascular diseases (e.g., hypertension and cerebrovascular disease) [ 49 , 50 ], and these vascular risk factors have been largely controlled in our statistical analyses. Our findings highlight that the subtype of dementia should be taken into consideration in risk stratification for dementia patients undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%